Synthesis and optical spectroscopy of the Eu- and Pr-doped glasses with SrO–2B2O3 composition - Padlyak, Bohdan; Grinberg, Marek; Kuklinski, Benedykt; Oseledchik, Yuriy; Smyrnov, Oleksandr; Kudryavtcev, Dmitriy; Prosvirnin, Andrew (Oficyna Wydawnicza Politechniki Wrocławskiej, 2010)
A series of Eu- and Pr-doped glasses with SrO–2B2O3 (or SrB4O7) composition were obtained and their spectroscopic properties were investigated. The SrB4O7 polycrystalline compounds were synthesised at T = 1300 K using high purity strontium carbonate (SrCO3) and boric acid (H3BO3). The Eu and Pr impurities were added to SrB4O7 compounds as Eu2O3 (amount: 0.167 at.%) and Pr2O3 (amounts: 0.05 and 0.25 at.%) oxides. The glass samples of high chemical purity and optical quality were obtained from corresponding polycrystalline compounds in the air atmosphere in platinum crucibles according to standard glass technology. Optical absorption, luminescence excitation and emission spectra of the Eu- and Pr-doped glasses with SrO–2B2O3 composition were investigated in the spectral range 300–800 nm at temperatures of 293 and 85 K. On the basis of optical spectra obtained and electron paramagnetic resonance (EPR) data analysis it is shown that Eu and Pr impurities are incorporated into the SrO–2B2O3 glass network as Eu3+ (4f6, 7F0) and Pr3+ (4f2, 3H4) ions, exclusively. All the observed transitions of the Eu3+ and Pr3+ centres in absorption and luminescence spectra were identified. The luminescence kinetics of Eu3+ and Pr3+ centres were investigated and analysed. The decay constants for main emission transitions in all samples investigated were obtained at room temperature. Peculiarities of incorporating the Eu3+ and Pr3+ activator ions in the glass with SrO–2B2O3 composition and their optical spectra are discussed in comparison with rare-earth doped polycrystalline compounds and single crystals with the same (SrB4O7) composition and other borate glasses.
Optica Applicata, Vol. 40, 2010, nr 2, s. 413-426
Keywords: optyka; borate glasses and crystals; Eu3+ centre; Pr3+ centre; optical absorption; luminescence; decay kinetics; local structure